2018
DOI: 10.1016/j.devcel.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps: The Biology of Chromatin Externalization

Abstract: Neutrophils are essential to the homeostatic mission of safeguarding host tissues, responding rapidly and diversely to breaches of the host's barriers to infection, and returning tissues to a sterile state. In response to specific stimuli, neutrophils extrude modified chromatin structures decorated with specific cytoplasmic and granular proteins called neutrophil extracellular traps (NETs). Several pathways lead to this unique form of cell death (NETosis). Extracellular chromatin may have evolved to defend euk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
259
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(270 citation statements)
references
References 149 publications
1
259
0
10
Order By: Relevance
“…Many studies have captured the role of intracellular ROS in the process of NET formation (39). Upon activation, the primary ROS produced by the neutrophils are superoxide anion and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have captured the role of intracellular ROS in the process of NET formation (39). Upon activation, the primary ROS produced by the neutrophils are superoxide anion and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The NETs contribute to pathogen elimination, and their microbicide activity has been studied mainly in the neutralization of bacteria, but their role in the response toward other types of pathogens is not yet clearly understood (54, 55). Sousa-Rocha et al demonstrated that trypomastigotes, and soluble T. cruzi antigens are capable of inducing NETs release on human neutrophils by activation of TLR2 and−4, and that this response depends on the activation of the respiratory burst and the production of reactive oxygen species.…”
Section: Innate Immunitymentioning
confidence: 99%
“…PMNs can also kill extracellular pathogens by degranulation, secretion of ROS, or the release of neutrophil extracellular traps (NETs). NETs consist of externalized decondensed chromatin decorated with granular proteins and histones to prevent the dissemination of pathogens . Serine proteases and histones provide antimicrobial activity against trapped pathogens.…”
Section: Intestinal and Invasive Nts Infectionsmentioning
confidence: 99%